Tetracycline antibiotics impair mitochondrial function and its experimental use confounds research - Chatzispyrou, Iliana A. (Cancer Res, 2015)
Tetracyclines, a class of antibiotics that target bacterial translation, are commonly used in research for inducible gene expression using Tet-ON/Tet-OFF systems. However, such tetracycline-inducible systems carry a risk. Given that mitochondria have a “bacterial” ancestry, these antibiotics also target mitochondrial translation and impair mitochondrial function. Indeed, treatment with doxycycline—a tetracycline derivative—disturbs mitochondrial proteostasis and metabolic activity, and induces widespread gene expression changes. Together, this affects physiology in well-established model systems ranging from cultured cells to simple organisms and to mice and plants. These changes are observed with doxycycline doses that are widely used to regulate gene expression. In light of these findings, and bearing in mind the conserved role of mitochondria in metabolism and whole organism homeostasis, we caution against the use of tetracyclines in experimental approaches. The use of newly developed tetracycline-based systems that are more sensitive could be an alternative; however, even if no overt mitochondrial toxicity is detected, widespread changes in gene expression may sensitize cells to the intended tetracycline-controlled loss- or gain-of-function, thereby introducing a “two-hit model”. This is highly relevant for cancer research, as mitochondrial metabolism holds a central position in the reallocation of nutrients for biomass production known as the Warburg effect.